2000
DOI: 10.1002/(sici)1097-0290(19960305)49:5<568::aid-bit10>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment of wheat straw using combined wet oxidation and alkaline hydrolysis resulting in convertible cellulose and hemicellulose

Abstract: The wet oxidation process of wheat straw has been studied as a pretreatment method to attain our main goal: To break down cellulose to glucose enzymatic, and secondly, to dissolve hemicellulose (e.g., for fermentation) without producing microbial inhibitors. Wet oxidation combined with base addition readily oxidizes lignin from wheat straw facilitating the polysaccharides for enzymatic hydrolysis. By using a specially constructed autoclave system, the wet oxidation process was optimized with respect to both re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
0
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(110 citation statements)
references
References 22 publications
2
91
0
4
Order By: Relevance
“…The wet oxidation method can be used for fractionation of lignocellulosics into solubilized hemicellulose fraction and a solid cellulose fraction susceptible to enzymatic saccharification. Bjerre et al [3] found that a combination of alkali and wet oxidation did not generate furfural and 5-hydroxymethyl furfural (HMF). Klinke et al [67] characterized the degradation products from alkaline wet oxidation (water, sodium carbonate, oxygen, high temperature, and pressure) of wheat straw.…”
Section: Pretreatment Of Hemicellulosementioning
confidence: 99%
“…The wet oxidation method can be used for fractionation of lignocellulosics into solubilized hemicellulose fraction and a solid cellulose fraction susceptible to enzymatic saccharification. Bjerre et al [3] found that a combination of alkali and wet oxidation did not generate furfural and 5-hydroxymethyl furfural (HMF). Klinke et al [67] characterized the degradation products from alkaline wet oxidation (water, sodium carbonate, oxygen, high temperature, and pressure) of wheat straw.…”
Section: Pretreatment Of Hemicellulosementioning
confidence: 99%
“…This type of pretreatment is effective at lignin degradation as well as hemicellulose solubilization (mainly as oligomers) resulting in a highly digestible pretreated solid fraction. This approach greatly reduces the amount of furfural and HMF produced if pH is controlled during pretreatment (Bjerre et al 1996).…”
Section: Pretreatmentmentioning
confidence: 99%
“…However, the solubilization of lignin is relatively low demonstrating that hydrothermal treatment does not significantly interact with lignin. In fact, the values obtained are even lower than the reported for the autohydrolysis of corn cobs under similar operational conditions [36] and also lower than other reported pre-treatments, specially those including either alkaline or oxidative treatments [37,38].…”
Section: Effect Of Autohydrolysis On the Products Yieldsmentioning
confidence: 99%